Embarking on a Research Odyssey: Factors Influencing Students’ Experiences of Successfully Completing a Research Project - Engelbrecht, Willy Hannes; Pramjeeth, Shamola (International Journal of African Higher Education, 2024)
Honours research plays a pivotal role in shaping individual academic careers, contributing to a nation’s collective knowledge reservoir and motivating students to undertake Masters and doctoral studies. This study identified the critical factors that enable students to successfully complete research projects. The positivist philosophical framework informed the quantitative research methodology employed at a private higher education institution in South Africa. Simple random sampling was used to select a sample of 172 students registered for NQF 8 programmes at the institution. Data were collected anonymously using an online questionnaire. Exploratory factor analysis, Pearson’s correlation and regression analysis were employed for statistical analysis. Four factors were identified: an enabling supervisor, constructive feedback, the research process, and support and guidance. The study found that successful completion of the research component of an honours degree depends on the expertise, support, and guidance provided by the supervisor throughout the research process.